Role of Hedging Mechanism in Maintaining Volatility Cash Flow and Growth Opportunity and Their Impact on Investor Reaction - Hartono, Hartono; Pasoloran, Oktavianus; Daromes, Fransiskus Eduardus (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 15 No 1 (2020), 2020)
This study aims to investigate the role of forward contract hedging in maintaining volatility cash flow and growth opportunity and its impact on investor reaction. The population in this study included 242 non-financial companies listed on the Indonesia Stock Exchange from 2013–2017. The sample was determined using purposive sampling, and path analysis was employed to analyze the data. Results show that forward contract hedging mediates the effects of volatility cash flow and growth opportunity on investor reaction. This research is expected to provide insights so that company management can improve performance properly and increase investor confidence through the application of hedging, thereby maintaining volatility cash flow and growth opportunity. Keywords: Cash flow volatility, growth opportunity, hedging forward contract, investor reaction.